Long noncoding RNA plasmacytoma variant translocation gene 1 promotes epithelial‐mesenchymal transition in osteosarcoma. Issue 1 (22nd September 2020) - Xun, Chuanhui; Jiang, Dawei; Tian, Zheng; Yunus, Akbar; Chen, Jiangtao
Abstract: Objective: Long noncoding RNAs (lncRNAs) are involved in the proliferation, migration, and invasion of tumors. In the current study, our aim was to explore the role of lncRNA plasmacytoma variant translocation gene 1 (PVT1) in osteosarcoma. Methods: Quantitative real‐time reverse transcription‐polymerase chain reaction was used to detect the expression of lncRNA PVT1 in osteosarcoma tissues and cells. The relationship between lncRNA PVT1 expression status and the prognosis of patients with osteosarcoma was analyzed. The effect of lncRNA PVT1 on the malignant biological behavior of osteosarcoma cells in vitro was also analyzed. Results: LncRNA PVT1 was upregulated in osteosarcoma. High lncRNA PVT1 expression indicated poor prognosis in patients with osteosarcoma. In vitro knockdown of lncRNA PVT1 inhibited the proliferation, migration, and invasion ability of osteosarcoma cells. In addition, we confirmed that lncRNA PVT1 affected the epithelial‐mesenchymal transition of osteosarcoma cells. Conclusion: LncRNA PVT1 is a potential therapeutic target for osteosarcoma. Abstract : LncRNA plasmacytoma variant translocation gene 1 (PVT1) promotes epithelial‐mesenchymal transition, proliferation, migration, and invasion of osteosarcoma cells.